Internet policy and Australia's Northern Territory Intervention - Ellie Rennie; Jake Goldenfein; Julian Thomas (Internet Policy Review, 2017)
In 2007, Australia's Commonwealth Government took a dramatic new approach to the governance of remote Indigenous communities. The 'Northern Territory Intervention' aimed to combat abuse and violence in remote Indigenous communities, and included far-reaching changes to welfare administration, employment programmes and policing. This paper considers a hitherto obscure aspect of the Intervention: the surveillance of publicly funded computers and internet use. Between 2007 and 2012, providers of internet and computer access facilities in the affected communities were required to audit and record computer use. In this paper we examine the legal and policy dimensions of this case of governmental surveillance, using interviews, published materials and documents obtained through freedom of information processes.
Keywords: 300; Digital divide; Surveillance; Computer surveillance; Child protection; Remote Indigenous communities